ANALYSIS OF WATER PRODUCTION POTENCIAL UNDER VARIOUS SCENARIO IN PANINGGAHAN-SINGKARAK WATERSHED - PUJILESTARI, N.; TARIGAN, S.D.; SUBAGYONO, KASDI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Paninggahan watershed is the sub watershed of the Singkarak Lake watershed. It has a largest part of managed forest in the upstream and the change of landuse from forest to mixture garden increasing rapidly. The study on the change of discharge related to the landuse change is the main focus of this research. The result shows that hydrological characteristic of Paninggahan watershed is still good, with the domination of secondary forest covering 53% of the watershed. Therefore this watershed still has large amount of water reserve. The result of monitoring landuse change from year 1984-2007, indicating that the rate of forest decreasing was 66 ha year-1 and the increasing of mixture garden was 39 ha year-1. The result of characteristic simulation discharge showed that forest degradation will increase total volume of discharge to 1.3 m3 s-1, whereas minimum debit will progressively decrease till 0.2 m3 s-1. The knowledge of the influence of landuse change due to decreasing of debit in the watershed becomes guidance for the continous watershed development.